Pollination services of mango flower pollinators - Abdul, Nurul Huda; M. R, Che Salmah; Abu Hassan, Ahmad; Hamdan, Ahmad; Abdul Razak, M. N. (Library of the University of Arizona, 2015)
Measuring wild pollinator services in agricultural production is very important in the context of sustainable management. In this study, we estimated the contribution of native pollinators to mango fruit set production of two mango cultivars Mangifera indica (L). cv. ‘Sala’ and ‘Chok Anan’. Visitation rates of pollinators on mango flowers and number of pollen grains adhering to their bodies determined pollinator efficiency for reproductive success of the crop. Chok Anan failed to produce any fruit set in the absence of pollinators. In natural condition, we found that Sala produced 4.8% fruit set per hermaphrodite flower while Chok Anan produced 3.1% per flower. Hand pollination tremendously increased fruit set of naturally pollinated flower for Sala (>100%), but only 33% for Chok Anan. Pollinator contribution to mango fruit set was estimated at 53% of total fruit set production. Our results highlighted the importance of insect pollinations in mango production. Large size flies Eristalinus spp. and Chrysomya spp. were found to be effective pollen carriers and visited more mango flowers compared with other flower visitors.